2015
DOI: 10.4103/2230-8229.163031
|View full text |Cite
|
Sign up to set email alerts
|

A clinic-based study of refractive errors, strabismus, and amblyopia in pediatric age-group

Abstract: Purpose:The purpose of this cross-sectional observational study was to determine the distribution and patterns of refractive errors, strabismus, and amblyopia in children seen at a pediatric eye care.Materials and Methods:The study was conducted in a Private Hospital in Dammam, Kingdom of Saudi Arabia, from March to July 2013. During this period, a total of 1350 children, aged 1–15 years were seen at this Center's Pediatric Ophthalmology Unit. All the children underwent complete ophthalmic examination with cyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
50
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(53 citation statements)
references
References 17 publications
1
50
1
1
Order By: Relevance
“…In this study, RE was found in 26.5% of the children. This frequency is higher than that in some studies conducted in KSA, 10 , 11 but less than that in some other studies also conducted in KSAs. 12 The reported prevalence of RE in different parts of the world show a variation from 7.0% to 19.8%, as shown in Table 3 .…”
Section: Discussioncontrasting
confidence: 69%
See 2 more Smart Citations
“…In this study, RE was found in 26.5% of the children. This frequency is higher than that in some studies conducted in KSA, 10 , 11 but less than that in some other studies also conducted in KSAs. 12 The reported prevalence of RE in different parts of the world show a variation from 7.0% to 19.8%, as shown in Table 3 .…”
Section: Discussioncontrasting
confidence: 69%
“…This is in contrast to previous studies in Al Hassa and Riyadh, KSA, where the errors were more prevalent in females than in males. 10 , 11 This study aimed to determine the types of childhood eye diseases in a Jazan and discuss the best ways to prevent it or prevent their effect on the vision of our children, as the institutions are working toward the longevity and welfare of the residents and healthcare is one of the important aspects in such a field.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study conducted in the Eastern province of Saudi Arabia emphasized the importance of public education and the early detection and management of strabismus to improve the educational opportunities and quality of life of these patients [16].…”
Section: Introductionmentioning
confidence: 99%
“…[7] However, in 2015, strabismus prevalence was much higher (38%) among clinic-attending children in Dammam. [8] Heterotropia is a clearly manifested strabismus form. The ocular deviation can be upward (hypertropia), downward (hypotropia), inward (esotropia), or outward (exotropia).…”
Section: Introductionmentioning
confidence: 99%